2019
DOI: 10.1002/cbic.201900408
|View full text |Cite
|
Sign up to set email alerts
|

Front Cover: Identification of mNeonGreen as a pH‐Dependent, Turn‐On Fluorescent Protein Sensor for Chloride (ChemBioChem 14/2019)

Abstract: Chloride-sensitivef luorescent proteins generated from laboratory evolution have ac haracteristict yrosine residue that interacts with ac hloride ion and p-stacks with the chromophore. However,t he engineered yellow-green fluorescent protein mNeonGreen lacks this interaction but still binds chloride, as seen in ar ecently reported crystal structure. Based on its unique coordination sphere, we were curious if chloride could influencet he opticalp roperties of mNeonGreen. Here, we present the structure-guided id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 27 publications
0
46
0
Order By: Relevance
“…However, the Cl − dissociation constant is out of the physiological range even at acidic pH, making it impractical for deployment at physiological pH. Similarly, the tetrameric YFP from Brachiostoma lanceolatum (lanYFP) has a Cl − -binding pocket (Tutol et al, 2019b). Monomerization of lanYFP maintains the Cl − -binding pocket to form mNeonGreen, a turn-on sensor for Cl − .…”
Section: Third Generationoptimizing the Old Discovering The Newmentioning
confidence: 99%
“…However, the Cl − dissociation constant is out of the physiological range even at acidic pH, making it impractical for deployment at physiological pH. Similarly, the tetrameric YFP from Brachiostoma lanceolatum (lanYFP) has a Cl − -binding pocket (Tutol et al, 2019b). Monomerization of lanYFP maintains the Cl − -binding pocket to form mNeonGreen, a turn-on sensor for Cl − .…”
Section: Third Generationoptimizing the Old Discovering The Newmentioning
confidence: 99%
“…[51] Based on this, we recently reported that chloride binding decreases the pKa of the chromophore and shifts the equilibrium from the non-fluorescent phenol state to the highly fluorescent phenolate state, generating a turn-on fluorescence response. [49] Furthermore, we attributed this unique sensing mechanism to a non-coordinating arginine residue, instead of a tyrosine residue, above the chromophore. Together, these homologues highlight how differences in the amino acid residues, within and outside of the chloride binding pocket and even in the chromophore, can influence sensor properties.…”
Section: Introductionmentioning
confidence: 96%
“…[42][43][44][45][46][47] Relative to these literature precedents, we have identified low sequence identity homologues that are also sensitive to chloride. [48,49] The chloride binding pocket in the naturally occurring yellow fluorescent protein from the jellyfish Phialidium sp. (phiYFP) is identical to that of avYFP-H148Q.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many sensor systems to detect chloride have been developed [32][33][34], many of which involve binding chloride by H-bonding or charge-charge interactions, while a few exploit the photochemical response of a metallo-receptor able to bind chloride [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%